2021
DOI: 10.1177/1477370820988830
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse in religious institutions: A comparative study based on sentences in Spain

Abstract: Child sexual abuse is a global problem that has several physical and psychological health implications for the victims. This study aimed to analyse the way criminal courts respond to allegations of child sexual abuse in religious institutions in Spain compared with cases of abuse committed in other institutional contexts. The sample is composed of 97 abusers from three institutional settings (religious institutions, educational centres, sports centres), responsible for a total of 335 child sexual abuse victims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
1
0
4
Order By: Relevance
“…Respecto a la metodología empleada (revisión sistemática de sentencias), no se puede afirmar que los repositorios jurisprudenciales recojan la totalidad de sentencias dictadas. Es más, esta dificultad se ha puesto de manifiesto en diversos estudios (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023. Si bien, existe consenso en que el CENDOJ contiene la mayoría de las sentencias dictadas por las Audiencias Provinciales (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023.…”
Section: Limitacionesunclassified
See 1 more Smart Citation
“…Respecto a la metodología empleada (revisión sistemática de sentencias), no se puede afirmar que los repositorios jurisprudenciales recojan la totalidad de sentencias dictadas. Es más, esta dificultad se ha puesto de manifiesto en diversos estudios (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023. Si bien, existe consenso en que el CENDOJ contiene la mayoría de las sentencias dictadas por las Audiencias Provinciales (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023.…”
Section: Limitacionesunclassified
“…Es más, esta dificultad se ha puesto de manifiesto en diversos estudios (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023. Si bien, existe consenso en que el CENDOJ contiene la mayoría de las sentencias dictadas por las Audiencias Provinciales (Stancu & Varona, 2017;Tamarit et al, 2014Tamarit et al, , 2022Tamarit et al, , 2023. Por otro lado, no existe un registro sistemático de los datos sociodemográficos de los implicados en el proceso.…”
Section: Limitacionesunclassified
“…yang merupakan orang yang dipercaya 2014). Dampak yang dialami korban juga bisa berupa PTSD atau bahkan hilangnya kepercayaan diri yang berakibat perusakan identitas (Fogler, Shipherd, Clarke, et al ;2008).…”
unclassified
“…Ketika korban melapor dan mencari pertolongan ke institusi yang terlibat, pengurus institusi cenderung tidak memberikan bantuan yang tepat dan terkesan mengabaikan korban (Wolfe, Francis, Straatman, Anna-Lee ;2004). 2014).…”
unclassified
“…A study by Pereda and Segura (2021) reported 38 adults (25 men and 13 women) having experienced sexual abuse when aged under 18 by representatives of the Catholic Church. A study by Tamarit et al (2021), which collected data on court cases referring to CSA committed by priests, members of religious congregations or ministers in other religious institutions, reported a total of 33 abuse cases (28 within the Catholic Church), involving 84 victims (61% boys), with 51.5% (17) abusing one victim and 48.5% (16) abusing multiple victims (ranging from 2 to 10).…”
mentioning
confidence: 99%